(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2013)
In total in the microphytobenthos of Kuchurgan estuary were found 122 species of algae, which belonged to 62 genera, 35 families, 21 orders, 9 classes and 6 divisions. First for this reservoirs 11 species algae were resulted. Among specific composition new species were found for the reservoir of North-Western Black Sea Coast (7 species) and rare for territory of Ukraine (6). After specific composition the representatives of division of Bacillariophyta (100 species) prevailed above the amount of species from the division of Cyanophyta (11), Chlorophyta (6), Streptophyta (2), Euglenophyta (2) and Dinophyta (1). Sorenson similarity coefficient-Czekanowski and Zhakara between algal flora Kuchurgan estuary and river Dniester were 0,57 and 0,40 respectively, and slightly higher than those between flora and Kuchurgan and Dniester estuaries (0,53 and 0,36) and Kuchurgan estuary and river Kuchurgan (0,47 and 0,31).